Bi-modular Charge System for 155 mm Calibre Ammunition - Jiří BERÁNEK (Wojskowa Akademia Techniczna, 2012)
This article provides background information on issues of a Bi-modular charge system designed for a 155 mm calibre artillery system. It summarizes the principles of design and knowledge gained during the developmental stage and provides information about the firing of modules in testing 100 mm TK V20 cannon.
Keywords: Ładunek prochowy do 155 mm amunicji